Extending Pollard class of factorable RSA modulus - Abd Ghafar, Amir Hamzah; Kamel Ariffin, Muhammad Rezal; Asbullah, Muhammad Asyraf (Institute for Mathematical Research, Universiti Putra Malaysia, 2018)
Pollard p − 1 method is able to solve integer factorization problem if the targeted composite number has small prime factors. This is a reason why implementation in key generation algorithm of RSA cryptosystem requires its primes, p and q not to be constituted by small primes. In this paper, we showed another method which targets N = pq and manipulates it against p − 1 and q − 1 structures. We remarked here that both p − 1 and q − 1 do not have small prime factors hence they can be generated without error by RSA libraries in current practice.